Speckle observations and orbits of multiple stars. - Tokovinin, Andrei; Everett, Mark E; Horch, Elliott P; Torres, Guillermo; Latham, David W (Astronomical Journal, 2019)
We report results of speckle-interferometric monitoring of visual hierarchical systems using the newly commissioned instrument NN-EXPLORE Exoplanet and Stellar Speckle Imager at the 3.5 m WIYN telescope. During one year, 390 measurements of 129 resolved subsystems were made, while some targets were unresolved. Using our astrometry and archival data, we computed 36 orbits (27 for the first time). Spectro-interferometric orbits of seven pairs are determined by combining positional measurements with radial velocities measured, mostly, with the Center for Astrophysics digital speedometers. For the hierarchical systems HIP 65026 (periods 49 and 1.23 yr) and HIP 85209 (periods 34 and 1.23 yr) we determined both the inner and the outer orbits using astrometry and radial velocities and measured the mutual orbit inclinations of 11.°3 ± 1.°0 and 12.°0 ± 3.°0, respectively. Four bright stars are resolved for the first time; two of those are triple systems. Several visual subsystems announced in the literature are shown to be spurious. We note that subsystems in compact hierarchies with outer separations less than 100 au tend to have less eccentric orbits compared to wider hierarchies. © 2019. The American Astronomical Society. All rights reserved..
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/097-296-370-783-044 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; ⛔ No DOI found

Speckle Interferometry at SOAR in 2018 - Tokovinin, Andrei; Mason, Brian D.; Mendez, Rene A.; Horch, Elliott P.; Briceño, Cesar (The Astronomical Journal, 2019)
The results of speckle interferometric observations at the 4.1 m Southern Astrophysical Research Telescope (SOAR) in 2018 are given, totaling 3097 measurements of 2427 resolved pairs with separations from 11 mas to 5.″9 (median 0.″15, magnitude difference up to 7 mag) and nonresolutions of 624 targets. This work continues our long-term speckle program. Its main goal is to monitor orbital motion of close binaries, including members of high-order hierarchies and Hipparcos pairs in the solar neighborhood. Also, pre-main-sequence stars in the Orion OB1 association were surveyed, resolving 26 out of 118 targets. In addition, we report the discovery of 35 new companions among field visual multiples (some of which are likely optical) and first-time resolutions of another 31 pairs. By combining the measurements given here with the published ones, we computed 76 orbits for the first time and updated orbital elements of 34 visual binaries. Their periods range from 0.65 to 1100 yr, and their quality varies from first tentative solutions of grade 5 to accurate elements of grades 1 and 2. Finally, a list of 53 spurious pairs discovered by various techniques and unresolved at SOAR is given. © 2019. The American Astronomical Society. All rights reserved..
28 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/174-863-467-125-303, pop00135 tex.type: [object Object]
Keywords: dept.phy; material: machine-readable tables; peer-reviewed

High-resolution imaging transit photometry of Kepler-13AB - Howell, Steve B.; Scott, Nicholas J.; Matson, Rachel A.; Horch, Elliott P.; Stephens, Andrew (The Astronomical Journal, 2019)
Using the high-resolution imaging instrument, 'Alopeke, at the Gemini-N telescope, we obtained simultaneous two-channel time-series observations of the binary exoplanet host star Kepler13-AB. Our optical observations were obtained during a transit event of the exoplanet Kepler-13b and light curves were produced using both speckle interferometric and aperture photometry techniques. Both techniques confirm that the transiting object orbits the star Kepler-13A while different transit depths are seen across the optical wavelength range, being ∼2 times deeper in the blue. These measurements, as well as mass determinations in the literature, are consistent with Kepler-13b being a highly irradiated gas giant with a bloated atmosphere. Our observations highlight the ability of high-resolution speckle imaging to not only assess binarity in exoplanet host stars but robustly determine which of the stars the transiting object actually orbits. © 2019. The American Astronomical Society. All rights reserved.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/165-359-450-283-875, pop00155 tex.type: [object Object]
Keywords: binaries: close; dept.phy; galaxies: photometry; instrumentation: high angular resolution; peer-reviewed; planetary systems; techniques: image processing

Orbits of 14 binaries based on 2018 SOAR speckle observations - Docobo, José A; Gomez, Jorge; Campo, Pedro P; Andrade, Manuel; Horch, Elliott P; Costa, Edgardo; Mendez, Rene A (Monthly Notices of the Royal Astronomical Society, 2019)
New data obtained during the 2018 March-April speckle run at the 4.1 m Southern Astrophysical Research (SOAR) telescope located at Cerro Pachón (Chile) allowed us to recalculate the orbits of the following visual binaries: WDS 06478+0020 (STT 157),WDS 07003-2207 (FIN 334Aa,Ab), WDS 07013-0906 (A 671), WDS 10174-5354 (CVN 16Aa,Ab), WDS 12155-3106 (RST 1658),WDS 12572+0818 (FIN 380),WDS 13044-1316 (HU 642),WDS 14243-3838 (RST 1785), WDS 16094-3103 (I 557), WDS 17115-1630 (HU 169), WDS 17119-0151 (LPM 629),WDS 17563 + 0259 (A 2189),WDS 18464-2755 (RST 2073), and WDS 19035-6845 (FIN 357). All but three of them are Southern stars. The recently published Gaia parallaxes were used to calculate the total mass of each of these systems, despite the fact that, in a few cases, only Hipparcos parallaxes were available. For two binaries, A 671 and RST 2073, there are no parallax data. However, in these cases, the masses deduced from the dynamical parallaxes provided relevant information. In addition, we also present the first orbit for each of three systems: HU 642, RST 1785, and RST 2073, using speckle measurements. Finally, using the dynamical parallaxes given by these orbits, we have been able to calculate the luminosity of these systems. Said luminosities allow us to indicate an approximate age for each of the components of the system, situating them within the HR diagram. © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-727-074-773-961, pop00143 tex.type: [object Object]
Keywords: Techniques: high angular resolution - astrometry - binaries; Visual - stars: fundamental parameters; dept.phy; peer-reviewed

Discovery of a compact companion to a nearby star - Kane, Stephen R.; Dalba, Paul A.; Horner, Jonathan; Li, Zhexing; Wittenmyer, Robert A.; Horch, Elliott P.; Howell, Steve B.; Everett, Mark E. (The Astrophysical Journal, 2019)
Radial velocity (RV) searches for exoplanets have surveyed many of the nearest and brightest stars for long-term velocity variations indicative of a companion body. Such surveys often detect high-amplitude velocity signatures of objects that lie outside the planetary mass regime, most commonly those of a low-mass star. Such stellar companions are frequently discarded as false-alarms to the main science goals of the survey, but high-resolution imaging techniques can be employed to either directly detect or place significant constraints on the nature of the companion object. Here, we present the discovery of a compact companion to the nearby star HD 118475. Our Anglo-Australian Telescope RV data allow the extraction of the full Keplerian orbit of the companion, which is found to have a minimum mass of 0.445 M o. Follow-up speckle imaging observations at the predicted time of maximum angular separation rule out a main-sequence star as the source of the RV signature at the 3.3σ significance level, implying that the companion must be a low-luminosity compact object, most likely a white dwarf. We provide an isochrone analysis combined with our data that constrain the possible inclinations of the binary orbit. We discuss the eccentric orbit of the companion in the context of tidal circularization timescales and show that non-circular orbit was likely inherited from the progenitor. Finally, we emphasize the need for utilizing such an observation method to further understand the demographics of white dwarf companions around nearby stars. © 2019. The American Astronomical Society. All rights reserved.
7 citations (Crossref) [2023-10-31]
Keywords: dept.phy; stars: individual (HD 118475); techniques: high angular resolution; techniques: radial velocities; white dwarfs

Detection of planetary and stellar companions to neighboring stars via a combination of radial velocity and direct imaging techniques - Kane, Stephen R.; Dalba, Paul A.; Li, Zhexing; Horch, Elliott P.; Hirsch, Lea A.; Horner, Jonathan; Wittenmyer, Robert A.; Howell, Steve B.; Everett, Mark E.; Butler, R. Paul; Tinney, Christopher G.; Carter, Brad D.; et al. (The Astronomical Journal, 2019)
The sensitivities of radial velocity (RV) surveys for exoplanet detection are extending to increasingly longer orbital periods, where companions with periods of several years are now being regularly discovered. Companions with orbital periods that exceed the duration of the survey manifest in the data as an incomplete orbit or linear trend, a feature that can either present as the sole detectable companion to the host star, or as an additional signal overlain on the signatures of previously discovered companion(s). A diagnostic that can confirm or constrain scenarios in which the trend is caused by an unseen stellar rather than planetary companion is the use of high-contrast imaging observations. Here, we present RV data from the Anglo-Australian Planet Search (AAPS) for 20 stars that show evidence of orbiting companions. Of these, six companions have resolved orbits, with three that lie in the planetary regime. Two of these (HD 92987b and HD 221420b) are new discoveries. Follow-up observations using the Differential Speckle Survey Instrument (DSSI) on the Gemini South telescope revealed that 5 of the 20 monitored companions are likely stellar in nature. We use the sensitivity of the AAPS and DSSI data to place constraints on the mass of the companions for the remaining systems. Our analysis shows that a planetary-mass companion provides the most likely self-consistent explanation of the data for many of the remaining systems.
27 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-295-956-723-177, pop00041 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: radial velocities

Observations of binary stars with the Differential Speckle Survey Instrument. VIII. Measures of metal-poor and triple stars from 2015 to 2018 - Horch, Elliott P.; Tokovinin, Andrei; Weiss, Samuel A.; Löbb, János; Casetti-Dinescu, Dana I.; Granucci, Nicole M.; Hess, Nicole M.; Everett, Mark E.; van Belle, Gerard T.; Winters, Jennifer G.; Nusdeo, Daniel A.; Henry, Todd J.; et al. (The Astronomical Journal, 2019)
We present 248 speckle observations of 43 binary and 19 trinary star systems chosen to make progress in two main areas of investigation: the fundamental properties of metal-poor stars and star formation mechanisms. The observations were taken at the Gemini North and South telescopes during the period 2015 July to 2018 April, mainly with the Differential Speckle Survey Instrument but also with a few early results from the new 'Alopeke speckle camera at Gemini North. We find that the astrometry and photometry of these observations as a whole are consistent with previous work at Gemini. We present five new visual orbits for systems important in understanding metal-poor stars, three of which have orbital periods of less than 4 yr, and we indicate the degree to which these and future observations can impact our knowledge of stellar properties and star formation. In particular, we find a decrease in mass at fixed spectral type for metal-poor stars versus their solar-metallicity analogs that is consistent with predictions that are made from current stellar models. © 2019. The American Astronomical Society. All rights reserved..
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-502-692-786-428, pop00025 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; stars: individual; techniques: high angular resolution; techniques: interferometric; techniques: photometric

TOI-150b and TOI-163b: two transiting hot Jupiters, one eccentric and one inflated, revealed by TESS near and at the edge of the JWST CVZ - Kossakowski, Diana; Espinoza, Néstor; Brahm, Rafael; Jordán, Andrés; Henning, Thomas; Rojas, Felipe; Kürster, Martin; Sarkis, Paula; Schlecker, Martin; Pozuelos, F. J.; Barkaoui, Khalid; Jehin, Emmanuel; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
We present the discovery of TYC9191-519-1b (TOI-150b, TIC 271893367) and HD271181b (TOI-163b, TIC 179317684), two hot Jupiters initially detected using 30-min cadence Transiting Exoplanet Survey Satellite (TESS) photometry from Sector 1 and thoroughly characterized through follow-up photometry (CHAT, Hazelwood, LCO/CTIO, El Sauce, TRAPPIST-S), high-resolution spectroscopy (FEROS, CORALIE), and speckle imaging (Gemini/DSSI), confirming the planetary nature of the two signals. A simultaneous joint fit of photometry and radial velocity using a new fitting package JULIET reveals that TOI-150b is a 1.254 ± 0.016 RJ, massive (2.61+−001912 MJ) hot Jupiter in a 5.857-d orbit, while TOI-163b is an inflated (RP = 1.478+−00022029 RJ, MP = 1.219 ± 0.11 MJ) hot Jupiter on a P = 4.231-d orbit; both planets orbit F-type stars. A particularly interesting result is that TOI-150b shows an eccentric orbit (e = 0.262+−00045037), which is quite uncommon among hot Jupiters. We estimate that this is consistent, however, with the circularization time-scale, which is slightly larger than the age of the system. These two hot Jupiters are both prime candidates for further characterization – in particular, both are excellent candidates for determining spin-orbit alignments via the Rossiter–McLaughlin (RM) effect and for characterizing atmospheric thermal structures using secondary eclipse observations considering they are both located closely to the James Webb Space Telescope (JWST) Continuous Viewing Zone (CVZ). © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.
15 citations (Crossref) [2023-10-31] Citation Key Alias: pop00004 tex.type: [object Object]
Keywords: Planets and satellites: detection; Stars: individual: HD271181; Stars: individual: TIC 179317684; Stars: individual: TIC 271893367; Stars: individual: TYC9191-519-1; Techniques: photometric; dept.phy; peer-reviewed

Near-resonance in a System of Sub-Neptunes from TESS - Quinn, Samuel N.; Becker, Juliette C.; Rodriguez, Joseph E.; Hadden, Sam; Huang, Chelsea X.; Morton, Timothy D.; Adams, Fred C.; Armstrong, David; Eastman, Jason D.; Horner, Jonathan; Kane, Stephen R.; Lissauer, Jack J.; et al. (The Astronomical Journal, 2019)
We report the Transiting Exoplanet Survey Satellite detection of a multi-planet system orbiting the V = 10.9 K0 dwarf TOI-125. We find evidence for up to five planets, with varying confidence. Three transit signals with high signal-to-noise ratio correspond to sub-Neptune-sized planets (2.76, 2.79, and 2.94 R⊕), and we statistically validate the planetary nature of the two inner planets (Pb = 4.65 days, Pc = 9.15 days). With only two transits observed, we report the outer object (P.03 = 19.98 days) as a planet candidate with high signal-to-noise ratio. We also detect a candidate transiting super-Earth (1.4 R⊕) with an orbital period of only 12.7 hr and a candidate Neptune-sized planet (4.2 R⊕) with a period of 13.28 days, both at low signal-to-noise ratio. This system is amenable to mass determination via radial velocities and transit-timing variations, and provides an opportunity to study planets of similar size while controlling for age and environment. The ratio of orbital periods between TOI-125 b and c (Pc/Pb = 1.97) is slightly lower than an exact 2:1 commensurability and is atypical of multiple planet systems from Kepler, which show a preference for period ratios just wide of first-order period ratios. A dynamical analysis refines the allowed parameter space through stability arguments and suggests that despite the nearly commensurate periods, the system is unlikely to be in resonance.
Keywords: dept.phy; peer-reviewed

The L 98-59 system: Three transiting, terrestrial-size planets orbiting a nearby M dwarf - Kostov, Veselin B.; Schlieder, Joshua E.; Barclay, Thomas; Quintana, Elisa V.; Colón, Knicole D.; Brande, Jonathan; Collins, Karen A.; Feinstein, Adina D.; Hadden, Samuel; Kane, Stephen R.; Kreidberg, Laura; Kruse, Ethan; et al. (The Astronomical Journal, 2019)
We report the Transiting Exoplanet Survey Satellite (TESS) discovery of three terrestrial-size planets transiting L 98-59 (TOI-175, TIC 307210830)—a bright M dwarf at a distance of 10.6 pc. Using the Gaia-measured distance and broadband photometry, we find that the host star is an M3 dwarf. Combined with the TESS transits from three sectors, the corresponding stellar parameters yield planet radii ranging from 0.8 R ⊕ to 1.6 R ⊕. All three planets have short orbital periods, ranging from 2.25 to 7.45 days with the outer pair just wide of a 2:1 period resonance. Diagnostic tests produced by the TESS Data Validation Report and the vetting package DAVE rule out common false-positive sources. These analyses, along with dedicated follow-up and the multiplicity of the system, lend confidence that the observed signals are caused by planets transiting L 98-59 and are not associated with other sources in the field. The L 98-59 system is interesting for a number of reasons: the host star is bright (V = 11.7 mag, K = 7.1 mag) and the planets are prime targets for further follow-up observations including precision radial-velocity mass measurements and future transit spectroscopy with the James Webb Space Telescope; the near-resonant configuration makes the system a laboratory to study planetary system dynamical evolution; and three planets of relatively similar size in the same system present an opportunity to study terrestrial planets where other variables (age, metallicity, etc.) can be held constant. L 98-59 will be observed in four more TESS sectors, which will provide a wealth of information on the three currently known planets and have the potential to reveal additional planets in the system.
80 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-363-095-757-409, pop00014 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planets and satellites: detection; stars: individual (TIC 307210830; TOI-175); techniques: photometric